Proximate Composition and Bacteriological Quality of Some Vegetables Sold in Parts of Taraba State, North-Eastern Nigeria - Hammuel, Chrinius; Tatah, Silas Verwiyeh; Briska,; Joyce (Darul Yasin Al Sys, 2024)
Market-sold fresh vegetables are subjected to a variety of contaminants or pollutants. The proliferation of microorganisms, like bacteria, in food is caused by growth-promoting environmental conditions. Determining the bacterial quality and proximate composition of some lettuce and cabbage sold in certain areas of Taraba State is the goal of this study. The samples were collected from Taraba North (Jalingo and Zing Markets) and Taraba South (Wukari and Donga Markets), and their nutritional makeup or proximate composition was determined using method adopted from Association of Official Analytical Chemists and bacterial count was carried out using pour plate method. The mean moisture content of the vegetables was higher in cabbage (95.41±0.04) and lettuce (96.82±0.52) from Donga. Lettuce and cabbage from Jalingo had ash content of 0.99±0.04 and 0.91±0.04 respectively. Cabbage (0.70±0.88) and lettuce (0.85±0.026) from Jalingo and Zing respectively were found to have a high protein composition. The cabbage samples from Wukari (0.60±0.04) and Jalingo (0.38±0.02) had higher mean lipid contents. Cabbage from Wukari had a higher mean fibre composition (3.95±0.10). The amount of carbohydrates in lettuce from Wukari was found to be higher (3.94±0.08). The total bacterial count mean values were higher in the cabbage sample collected from the Zing market (1.43×107±1.43×105) and higher in the fresh lettuce sample collected from Wukari market (1.52×107±4.9×105). Bacterial contamination can cause vegetables to deteriorate and lose important nutrients. Vegetables sold in markets should therefore be properly washed and prepared before eating.